Alignment between glioblastoma internal clock and environmental cues ameliorates survival in Drosophila. - Jarabo, P.; Barredo, C.G.; de Pablo, C.; Casas-Tinto, S.; Martin, F.A. (Communications biology, 2022)
Virtually every single living organism on Earth shows a circadian (i.e. "approximately a day") internal rhythm that is coordinated with planet rotation (i.e. 24 hours). External cues synchronize the central clock of the organism. Consequences of biological rhythm disruptions have been extensively studied on cancer. Still, mechanisms underlying these alterations, and how they favor tumor development remain largely unknown. Here, we show that glioblastoma-induced neurodegeneration also causes circadian alterations in Drosophila. Preventing neurodegeneration in all neurons by genetic means reestablishes normal biological rhythms. Interestingly, in early stages of tumor development, the central pacemaker lengthens its period, whereas in later stages this is severely disrupted. The re-adjustment of the external light:dark period to longer glioblastoma-induced internal rhythms delays glioblastoma progression and ameliorates associated deleterious effects, even after the tumor onset.